The Spirit in creation. Issue 1 (15th January 2014) - Williams, David T.
Abstract: The result of the Arian controversy was the affirmation of the total equality of the trinitarian persons. This led to the realisation that all three persons of the Trinity are involved in every external action of God. Despite this, the role of the Holy Spirit in creation has not been clear, partly due to few specific references in the creation narratives. However, it may be suggested that the Spirit does not act in the creation of matter, which is the role of the second person, but in the provision of the underlying form and order necessary for very existence, and specifically for the dynamic interaction which is of the essence of life, as in the second account of the creation of the man (Gen 2). This reflects the fact that the action of the Spirit is also essential in salvation to link Christ's work on the cross to the believer. While separation is a feature of the Genesis creation narrative, this is balanced by the interrelating of what had been created. So, although Christian theology has commonly seen the world as 'spirit'-less, restricting the action of the Holy Spirit to the church, this would be understood as referring to the limitation of his direct action. His immanent presence is nevertheless essential in all for very existence. The Spirit is not in the world, but underlies it. Creation may be seen as a theistic act, by transcendent intervention to give matter, and giving interaction in immanent presence. The nature of the world therefore reflects the theistic nature of God, involving both distinction and relating. Indeed it then reflects the trinitarian nature of the creator, in which the persons maintain their absolute distinction at the same time as their total equality through the interaction of perichōrēsis, specifically enabled by the action of the Spirit as generating and undergirding relationship. The parallel between the created and the creator is seen especially insofar as the discrete elements of matter interrelate to give form and interaction. It is in their interaction that the elements of creation fulfil their purpose, and so specifically that humanity reflects its nature as created in imago Dei .